CONTEMPORARY ISLAMIC THOUGHT and its PLACE in The EDUCATION of GENERATION (Islamic Sciences Journal, 2023)
Praise be to Allah , prayer and peace be upon the Messengers and The God of the good and virtuous and his family granite blessed , I say at the outset that the individual is the title of the civilization of any : a nation want to transcend their personnel to Your Excellency in thought and development , and our generation are the nucleus of that civilization in community building ; So hurt my research in the maturing of thought Salim + behavior upright = civilization ; Therefore, I find that contemporary Islamic thought is the engine of the systematic construction of generation , thought and is the pulse of the times and Immunology intellectual sincerity Malik bin Nabi " God's mercy " when he said: "It's before the story of every colonizing there story of a people met for incapacity , not exaggerating when we say that authoritarianism and dictatorship is the result of ignorance and shed a lack of awareness , and the spread of the culture of subservience and subordination in the communities , what is the value assigned someone else to think about his place ? .And decide without him , " thought and is the title of civilization , and generally has included research on the introduction and three sections included first topic: the general framework , but for the Study of the second handled : Islamic Thought curriculum thinking , and included a third topic: Islamic thought approach regulate the behavior of the individual, and also contained a conclusion and recommendations and a list of sources and references.
Keywords: Islamic Thought , Contemporary , Generation Breeding, Educational Curriculum Quran .